Communication, Information, and Education on Self-Awareness about Marriage Age Maturation among Adolescent Girls (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
Indonesia has the highest rate of early marriage in the world, according to a UNICEF study, placing 15th out of 63 countries. Child marriage will make it much harder for Indonesia to obtain a high human development index and meet sustainable development goals. To determine whether Communication, Information, and Education (CIE) regarding maturing age at marriage through the Interprofessional Education (IPE) approach affected the students' self-awareness. An experimental study with one group pre-test and post-test design was conducted on 121 participants. They were selected using random sampling from 16-30th August 2021 in Hidayatul Mubtadiat Islamic boarding school, Puri sub-district, Mojokerto district, East Java province, Indonesia. The intervention group attended a workshop led by a religious leader, psychologist, and maternity nursing lecturer, completed by a follow-up program. The data was collected using the self-awareness questionnaire modified from the Situational Self-Awareness Scale (SSAS). IBM SPSS (v.28) was used to analyze the data, including statistical tests such as descriptive statistics and a paired t-test for comparing the mean scores. A 5% level of significance was considered. After interventions, there was a significant self-awareness score improvement (p-value 0.000 and T value = -15.9). The participants had self-awareness in the good category of 60.3 %. Up from 17.4 % before the intervention with a change in mean + standard deviation (SD) pre-post 57.8 + 7.2 to 66.2 + 7.0. Meanwhile, the number of participants who had less self-awareness before the intervention (42.1%) decreased to 5% after the intervention. The study's findings verified the effectiveness of the CIE strategy to enhance self-awareness among adolescent girls using the IPE method. The supply of CIE on the maturity of marriage age with an interprofessional education approach is the proper step to raise adolescents' self-awareness in the right decision-making process. So that they can avoid early marriage deliberately and independently.